2019
DOI: 10.1016/j.jtho.2019.03.030
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Radiation Therapy for the Treatment of Malignant Pleural Mesothelioma: Expert Opinion from the National Cancer Institute Thoracic Malignancy Steering Committee, International Association for the Study of Lung Cancer, and Mesothelioma Applied Research Foundation

Abstract: Introduction: Detailed guidelines regarding the use of radiation therapy for malignant pleural mesothelioma (MPM) are currently lacking because of the rarity of the disease, the wide spectrum of clinical presentations, and the paucity of high-level data on individual treatment approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 44 publications
2
41
0
1
Order By: Relevance
“…The results from this trial aligned those from a meta-analysis of five randomized controlled trials, which concluded that prophylactic radiotherapy did not reduce procedure site recurrence (29). Consensus recommendations from a multidisciplinary team of mesothelioma expects do not recommend radiation to prevent PTMs, with the exception of patients with histologically confirmed positive procedure tracts (18). More research is warranted on specifically for the population with epithelioid tumors to determine if there is any benefit.…”
Section: Role Of Radiation In Procedures Tract Metastasessupporting
confidence: 55%
See 2 more Smart Citations
“…The results from this trial aligned those from a meta-analysis of five randomized controlled trials, which concluded that prophylactic radiotherapy did not reduce procedure site recurrence (29). Consensus recommendations from a multidisciplinary team of mesothelioma expects do not recommend radiation to prevent PTMs, with the exception of patients with histologically confirmed positive procedure tracts (18). More research is warranted on specifically for the population with epithelioid tumors to determine if there is any benefit.…”
Section: Role Of Radiation In Procedures Tract Metastasessupporting
confidence: 55%
“…Progression-free survival remained low largely due to a high distant relapse rate of 81%, with the majority of this being outside the radiotherapy field. Additionally, while authors concluded that results did not support the routine use of radiation therapy after EPP, the trial had several limitations including lack of statistical power, and experts have continued to recommend radiation therapy in conjunction with EPP despite the results of this trial (18). Table 1 summarizes the above studies and reported median overall survival for patients undergoing EPP and subsequent radiotherapy.…”
Section: Post-operative Radiotherapy After Eppmentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor: Much-needed consensus recommendations on the use of radiation therapy for malignant pleural mesothelioma (MPM) were recently provided by an expert panel. 1 The authors focused their efforts to standardize/optimize radical treatments, with adjuvant radiotherapy delivered before or after extrapleural pneumonectomy or after pleurectomy/decortication. However, new studies are opening the way to reconsider a more aggressive approach in the palliative setting in view of preliminary evidence on increasing patients' overall survival.…”
mentioning
confidence: 99%
“…We thank Fodor et al 1 for their thoughtful letter pertaining to our recent expert opinion paper on radiation therapy in the treatment of malignant pleural mesothelioma (MPM). 2 We are also aware of the promising results of the phase III randomized trial by Minatel et al, 3 suggesting that although follow-up is limited, a more aggressive radical hemithoracic radiotherapy (RHR) approach with a simultaneous integrated boost (SIB) may improve survival outcomes compared with palliative radiation therapy to a limited treatment area. Toxicity rates in the RHR group were also notable, with approximately 10% of patients experiencing grade 3 or higher pneumonitis and another 10% experiencing grade 4 late respiratory failure requiring oxygen.…”
Section: To the Editormentioning
confidence: 99%